Evaluasi Mutu dan Penerimaan Panelis terhadap Rainbow Cake yang Dibuat dari Tepung Terigu dan Pati Sagu Lokal - Usman Pato; Vonny Setiaries Johan; Arnizam Arnizam (Agricultural Faculty, 2014)
Riau is one of the sago starch-producing province in Indonesia. Nowadays, sago starch has been utilized to produce various types of tradisional foods. The aim of this study was to compare the quality of rainbow cake produced by the addition of 30% sago starch and rainbow cake using 100% wheat flour and to evaluate panelist acceptance of these rainbow cakes. This study used a Completely Randomized Design (CRD) with two treatments and eight replications thus obtained 16 experimental units. The treatments were TS1 (100% wheat and 0%sago starch) and TS2 (70% wheat flour and 30%sago starch). The parameters observed were moisture, ash, sucrose and fat contents as well as panelist acceptance test. The results of this study indicated that rainbow cake of TS1 treatment (100% wheat flour and 0%sago starch) had no significant difference with rainbow cake of TS2 treatment (70% wheat flour and 30% sago starch) in case of ash and sucrose contents, but had significant effect on moisture and fat contents of rainbow cake. Based on the panelist acceptance test, the rainbow cake made from 70% wheat flour and sago starch 30% could be accepted by panelists similar to commercial rainbow cake.